A study on the influence of COVID-19 on university students online food purchasing behavior in Bangladesh - Mahadi, Kazi Ahbab (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.